Fatal infections caused by methicillin‐resistant Staphylococcus aureus of clonal complex 398: case presentations and molecular epidemiology. Issue 2 (April 2015) - Berning, Christiane; Lanckohr, Christian; Baumgartner, Helmut; Drescher, Mike; Becker, Karsten; Peters, Georg; Köck, Robin; Kahl, Barbara C.
Abstract : Introduction: Methicillin‐resistant Staphylococcus aureus (MRSA) of clonal complex (CC) 398 has emerged in livestock across Europe over the past 10 years. Case presentation: Case 1 was a patient with a history of destructive chronic polyarthritis and immunosuppressive therapy who presented with dyspnoea and pain in the shoulders, back and hips. Microbiological analysis of tissue samples, punctures and blood cultures revealed MRSA. Echocardiography showed mitral valve endocarditis. The patient was treated with daptomycin and fosfomycin. Case 2 was a patient presenting with pneumonia after lung transplantation. Respiratory specimens and perianal swabs revealed MRSA. The patient was treated with teicoplanin and linezolid. The patients did not recover from their infections and died. The isolates belonged to spa types t2576 (case 1) and t011 (case 2), to sequence type 398 within CC398 as determined by multilocus sequence typing and to staphylococcal cassette chromosome mec type 5. An IdentiBAC Microarray revealed the absence of a bacteriophage integrating into the hlb gene indicative of the livestock origin of the isolates. In 2013, 170 of 534 MRSA cases (31.8 %) among inpatients of the University Hospital Münster, Germany, were caused by closely related spa types clustering in one spa ‐CC indicative of CC398. Two of 12 MRSA isolates from blood cultures (16.7 %) were caused by isolates associated with MRSA CC398. Conclusion: Livestock‐associated MRSA CC398 is emerging as a cause of human infections. This observation is alarming and should inspire future efforts to control MRSA in livestock, forestall community spread and monitor changes of the occurrence of MRSA CC398 among cases of human infections.